PATRIARCHY AND POWERLESS: THE HIERARCHY IN THE CRYING OF LOT 49 - Dinie, Nida Najah; Fauziyyah, Nurkhalistiani; Anugrah, Zidni Dinia; Nurholis, Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
The Crying of Lot 49 is one of Thomas Pynchon’s novel that offers a detailed analysis of power, conspiracy, and hierarchy within contemporary society, investigating how concealed systems influence individual lives. The story follows Oedipa Maas, who uncovers a realm filled with secret symbols and clandestine networks, particularly the Trystero postal system, which challenges established views on societal control. The narrative emphasizes hierarchical themes related to gender, class, and authority, linking them to the societal transformations following World War II and the manipulation of power dynamics. Pynchon critiques conventional gender roles through Oedipa's portrayal as a passive housewife and examines patriarchy in her interactions with male figures of authority. Symbols like the